Efektivitas Strategi Pembelajaran Klinik Metode SNAPPS (Summarize, Narrow, Analyze, Proba, Plan) Terhadap Penalaran Klinis Pada Mahasiswa Praktek Klinik : Systematic Review - Hani Tuasikal; Raihany Sholihatul Mukaromah (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2019)
Clinical reasoning (clinical reasoning) is a special skill that must be possessed by a health worker, one of whom is a nurse (Noorman, 2005). This skill is one example of critical thinking skills. The clinical learning strategy that can be used is the SNAPPS method. The purpose of this systematic review is to find out the clinical learning strategy of the SNAPPS method for clinical reasoning in clinical practice students. Articles searched through Ebsco, Sciencedirect, PubMed and Google search are performed using advanced search with the keywords SNAPPS, clinical Reasioning and student clinical practice. The study inclusion criterion was limited search of 2005-2015 which can be accessed fulltext in pdf format with RCT and Quasi Experiment designs conducted on clinical practice students. The intervention in the form of SNAPPS method with the comparison of usual and customary methods with outcomes measures the ability of clinical reasoning in clinical practice students. Exclusion criteria include only abstracts and no English. The appropriate article is then analyzed using the critical appraisal tool that is appropriate for the results of the RCT and QE research to assess the quality of the study. Data extracted from articles and then grouped to be discussed and concluded. The results of 3 articles obtained 2 RCT (Randomized Control Trials) and 1 Quasi Experiment article. The results of the discussion showed that the SNAPPS method is more effective than the usual and customary group methods in improving clinical reasoning abilities for students who practice clinics. The author recommends to the education party to be able to implement the clinical learning method of the SNAAPS method and it is recommended to further researchers to conduct further research so that it can enrich the evidence scientifically.